Kefir alters craniomandibular bone development in rats fed excess dose of high fructose corn syrup - Ekici, O.; Aslan, E.; Guzel, H.; Korkmaz, O. A.; Sadi, G.; Gurol, A. M.; Boyaci, M. G.; Pektas, M. B. (SPRINGER JAPAN KK, 2022)
Introduction Dietary high fructose corn syrup (HFCS) is involved in the pathogenesis of oral diseases as well as metabolic diseases. The aim of this study was to investigate the effects of HFCS-feeding on the craniomandibular bone development at an early age and also the potential of milk kefir for preventive treatment. Materials and methods In this study, Control, Kefir, HFCS, and HFCS plus Kefir groups were formed; kefir was given by gastric gavage, while HFCS (20% beverages) was given in drinking water; for 8 weeks. Results Based on morphological evaluations, immunohistochemical, and gene expression results, it was clearly determined that excess dose of HFCS consumption decreased osteoblastic activity in craniomandibular bones while increasing osteoclastic activity. However, it has been determined that the intake of kefir with the HFCS-feeding greatly suppresses the effects of HFCS on bone tissues. Conclusion In conclusion, dietary the excess dose of HFCS at an early age has been observed to pose a risk for cranial and mandible bone development. The healing effects of kefir may be a new approach to the treatment via kefir consumption in young's.
Keywords: HFCS; Kefir; Craniomandibular bone; RANKL; RUNX2; METABOLIC SYNDROME; INSULIN-RESISTANCE; FEMORAL-HEAD; DYSFUNCTION; Endocrinology & Metabolism; Research & Experimental Medicine